Is the Ninth Circuit a Liberal Environmental Activist Court?. (2nd April 2016) - Keele, Denise M.; Malmsheimer, Robert W.
ABSTRACT: We test the proposition that litigation outcomes in the Ninth Circuit are significantly more activist and liberal on all federal court cases filed over a 20-year time period in which a U.S. executive agency, the USDA Forest Service, was a defendant in a lawsuit challenging a land management decision. Our results reveal that the Ninth Circuit was not significantly more likely to reverse agency decisions in the liberal direction; however, the District Courts located in the Ninth Circuit were. Additionally, opinions that all Circuits', including the Ninth Circuit, judicial panels opted to publish were significantly more likely to reverse agency action and be in the liberal direction. One consistent and statistically significant finding was that any reversal of agency action, not just those that are published, were much more likely to be in the liberal direction.